Expression of PTEN and β-Catenin and Their Relationship With Clinicopathological and Prognostic Factors in Endometrioid Type Endometrial Cancer. Issue 3 (1st March 2016) - Sal, Veysel; Demirkiran, Fuat; Erenel, Hakan; Tokgozoglu, Nedim; Kahramanoglu, Ilker; Bese, Tugan; Turan, Hasan; Sofiyeva, Nigar; Calay, Zerrin; Arvas, Macit; Guralp, Onur
Abstract : Objective: The aim of this study was to investigate rates of expression of PTEN (phosphatase and tensin homolog deleted on chromosome 10) and β-catenin and their relationship with clinicopathological and prognostic factors in endometrioid type endometrial cancer (EC). Methods and Materials: PTEN and β-catenin expressions of 59 operated patients with EC between January 2000 and December 2008 and followed-up until December 2014 in Cerrahpasa School of Medicine, Gynecologic Oncology Division, were evaluated retrospectively. Clinical data were obtained from patient files, and pathological data were obtained from pathology records. Each patient had 4 paraffin sections of tumoral tissue. These sections were stained by immunohistochemical methods. Clinical features and postoperative histopathologic findings were analyzed using Fisher exact test or the χ 2 test as appropriate. The Kaplan-Meier method was used to generate the survival curves. Results: During median follow-up of 102 months, tumor recurrence and disease-related mortality were observed in 10 (16.9%) and 7 (11.9%) cases, respectively. Immunohistochemical staining of PTEN and β-catenin were positive in 61% and 69.5% of all cases, respectively. Positive staining of PTEN was positively correlated with myometrial invasion ( P = 0.02). There was no correlation between β-catenin and clinicopathological factors. PTEN or β-catenin positivity were not significant prognostic factors for 5-year overall survival ( P = 0.37, P = 0.62, respectively) and 5-year disease-free survival ( P = 0.28, P = 0.58, respectively). Conclusions: PTEN and β-catenin expressions cannot be used to determine prognosis in patients with EC as PTEN and β-catenin staining status were found to have no significant effect on 5-year overall survival and disease-free survival. Positive staining of PTEN may be associated with increased myometrial invasion. Meta-analyses and broader studies are needed to evaluate the prognostic value of PTEN and β-catenin in EC.